Clinical efficacy of resveratrol as an adjuvant with meloxican in the treatment of knee osteoarthritis patients: A double-blind, randomised, placebo-controlled trial - Bushra Hassan Marouf; Saad Abdulrahman Hussain; Ziyad Serdar Ali; Runj Simko Ahmmad (Universidade de São Paulo, 2019)
The present study aimed to evaluate the effect of the adjuvant use of resveratrol with meloxicam on the clinical scores of knee OA patients. This was a double-blind placebo-controlled randomised trial involving 100 patients with knee osteoarthritis performed at the Shar Teaching Hospital, Sulaimani General Hospital and Specialised Rheumatology Center, Sulaimani City from December 2016 to September 2017. The efficacy of the treatment was evaluated by measuring the changes from baseline in the KOOS score, WOMAC index, and VAS-100 score after 90 days of treatment. Resveratrol significantly improves the knee OA pain and associated symptoms compared with placebo, and both clinical scores were found to be eligible for following treatment outcomes. In conclusion, resveratrol, when used in combination with meloxicam, improves pain and symptom scores in patients with mild-to-moderate knee OA compared with placebo. The intervention with a dietary supplement may significantly impact the pain and overall quality of life in patients with knee OA.